Model Evaluasi Pembelajaran Bahasa Arab bagi Siswa Disabilitas di Madrasah Ibtidaiyah Inklusi - Yuslam, Yuslam Yuslam; Harimi, Abdal Chaqil; Nurkhikmah, Tsalisatun (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research wanted to know the characteristics of students with disabilities in Madrasah and also analyzed Evaluation Models in Inclusive Class. The type of research used is qualitative research with a case study model. Data collection techniques used were interviews, observation, and documentation. The data sources determined using a purposive sampling technique were the head of the madrasah, the Arabic language subject teacher, and students with disabilities in the class. Subjects of this research were the Head of the Madrasah, Teachers, and Students with disabilities. Data was analyzed with reduction, display, and verification by Mile and Huberman. This research shows that students with disabilities in the two madrasas are diverse. MI Salafiyah Kebarongan has 13 disabled students with various types of disabilities, while MI Maaraif NU Ciberem Sumbang has 23 disabled students with various types of disabilities. The madrasah does not immediately issue the determination of the type of disability but is also based on a recommendation from the Banyumas District Hospital; the problems found in inclusive madrasas tend to be non-linguistic problems which include differences in student characteristics, teachers' lack of understanding in dealing with student characteristics, and a lack of inclusiveness training for teachers in these madrasas; The evaluation model combined with the Inclusive Evaluation Model which was adapted to the Student with disabilities in class by modifying the exam process in class.